IMPROVING STUDENT’S READING COMPREHENSION THROUGH SCANNING TECHNIQUE AT THE SECOND GRADE OF THE JUNIOR HIGH SCHOOL - Revaldo Irenius Djuma; Noldy Palengkahu; Maikel B.G Sanger (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of the research paper, "Enhancing Students' Reading Comprehension Through the Scanning Technique," was to look at the usage of scanning techniques in improving students' reading comprehension at SMP Berea Tondano. This study included twenty-eight eighth-grade pupils. The research approach used was classroom action research. The information was acquired from a variety of sources, including observations at each cycle meeting and a questionnaire. The average scores in cycle two (Y1 = 18,5) were higher than in cycle one (Y1 = 5,95), according to the findings of this study. Furthermore, according to the results of the students' survey, 77 percent of students chose "agree" and 33 percent chose "very agree" to employ scanning approach in comprehending narative texts. This research is expected to aid in the teaching of English. Furthermore, it is advised that future scholars look at the usage of scanning techniques in other books. Keywords : Experiments, reading, comprehension, scanning technique